PERFORMANCE OF SCHOOL EMPLOYEES AT SMAN 2 CADET BHAYANGKARA EAST JAVA - Naufal Yoga Fahreza; Arik Susbiyani; Toni Herlambang; Ni Nyoman Putu Martini (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2026)
This study aims to analyze the influence of discipline, competence, and creativity on employee performance, with job satisfaction serving as an intervening variable at SMAN 2 Taruna Bhayangkara, East Java. A quantitative approach was employed, utilizing Partial Least Squares analysis (WarpPLS 8.0) based on data collected from 107 respondents, including teachers, administrative staff, and police supervisors. The findings revealed that discipline and competence had a positive and significant effect on job satisfaction, whereas creativity did not. Both discipline and competence also significantly impacted employee performance, while creativity showed no immediate effect. Additionally, job satisfaction partially mediates the relationship between discipline and competence and employee performance but does not mediate the influence of creativity on performance. Thus, competence is the most dominant factor affecting employee performance, while job satisfaction strengthens the effects of discipline and competence. This research highlights the importance of competency development, strict enforcement of discipline, and innovation mechanisms to continuously improve employee performance.